Implementation of Antimicrobial Stewardship Interventions in Primary Care: Acute Bacterial Rhinosinusitis Treatment Strategies - Mackenzi Meier; Kristen Pierce; Rachel Musgrove; Zachary Holmes; Akeia Harris; Ndifreke Veronica Asuquo; Lilia Z. Macias-Moriarity; Ashley Woodhouse (SAGE Publishing, 2023)
Background: The highest prescribing rates for antibiotics occur in primary care, therefore, ambulatory care pharmacist interventions could play a major role in preventing overuse and misuse of antibiotics. Delegated pharmacists in the SJC primary care setting guided 3 activities with a goal of positively impacting prescribing patterns: monthly webinars provided by Agency for Healthcare Research and Quality (AHRQ), quarterly reporting to physicians of antibiotic prescribing patterns, and development of a clinical decision-making support tool for antibiotic prescribing. Methods: Retrospective, observational data was collected to evaluate antibiotic prescribing patterns in patients diagnosed with acute sinusitis both before initiatives were implemented (July 1, 2019 through June 30, 2020) and after the initiatives were implemented (April 1, 2022 through June 30, 2022). Results: A total of 675 patients were diagnosed with acute bacterial sinusitis during the specified time frame. Of these, 138 patients were excluded. A total of 279 antibiotics were prescribed in the preintervention group out of 298 patient encounters (93.6%) and 225 antibiotics were prescribed in the post-intervention group out of 244 patient encounters (92.9%) ( p  = .26). Although the primary outcome was not statistically significant, a significant reduction in patients treated with fluoroquinolones was noted, with 59/298 (20%) of those being prescribed in the pre-intervention group and 20/244 (8%) in the post intervention group ( P  = .02). Conclusions: While pharmacist-led antimicrobial stewardship interventions in primary care did not result in a decrease in the overall prescription of antibiotics for acute sinusitis, our study did reveal a notable reduction in the use of fluoroquinolones. This finding highlights a promising avenue for expanding the role of ambulatory care pharmacists.